A bibliometric analysis of venture capital research - Cancino, Christian A. (2018)
Purpose: The purpose of this study is to present the evolution of academic research in venture capital (VC) research between 1990 and 2014. Design/methodology/approach: The study analyzes the most influential journals in VC research by analyzing papers which were published on the Web of Science database. Findings: Results show a steady increasing rate of VC research during the past 25 years. The paper reports the 40 academic journals that permanently publish articles about VC research. Originality/value: The main contribution of this work is to develop a general overview of the leading journals in VC research which leads to the development of a future research agenda for bibliometric analysis such as the review of the most productive and influential authors universities and countries in VC research.